James Fenimore Cooper's Wyandotté: A new variant of the vanishing Indian - Peprník, Michal (Bohemica Olomucensia, 2019)
The paper challenges the conventional critical assumption that James Fenimore Cooper was recycling the myth of the Noble and Ignoble Savage and the stereotype of the Good and Bad Indian. The paper takes as a starting point the discourse of savagism (Roy Harvey Pearce), in which the opposites are blended into a single mixed type, neither purely noble or ignoble, good or bad, the so called Vanishing Indian. The paper demonstrates that Cooper created a greater variety of types of the Vanishing Indian and that their typology was the result of a largely autonomous (semiotic) process of variation, based on new combinations of already existing traits. Moreover, in his late novels, most clearly in Wyandotté (1843) Cooper even probed the options of moving beyond the semantic field of the Vanishing Indian towards a more mimetic concept of culturally assimilated Indian.
Keywords: Noble and Ignoble Savage; Vanishing Indian; James Fenimore Cooper; discourse of savagism; Wyandotté; or; the Hutted Knoll. A Tale